(3GdLfi GdOGfj aj MQha GdeYGfjs - (3GdMSf Hf bGSe Hf YHO Gddg GdeQGOj GdeUQj, HOQ GdOjf CHh eMeO, GHf Ge bGSe , J (B749 (3g` s ((3YHOGdcQje Hf SdeGf GdKbaj GdTGaYj s)
(3ChdgG (B:s
(3hHYO, aEfg deG cGfJ ebGUO cdGe GdYQH Ydi GNJdGa Ufhag eHfjkG CcKQgG Ydi eYGfj MQhag s
(3BNQgG (B:s
(3hEfeG CgedJ PcQgG gfGc dTgQJgG hZQGHI Gdbhd HMQaJjgG hddcdGe YdjgG ehVY gh Cdjb Hg ef gPG GdcJGH, hGddg Gdehab ced cJGH s
(3fSNI cJHJ Yf fSNI HNW GdeDdas
(3HgG fbU aj GdOGNd ef hQbI (B40-50 (3hHgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B211 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B271s
Keywords: (3GdfMhs